Edukasi Gizi Seimbang pada Anak Usia Sekolah - Desiana Firdaus; Amanda Safiera Ameline; Hubi Rahmat Andika; Roiyan One Febriani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Nutritional problems among school-aged children remain a significant public health concern in Indonesia, including inadequate dietary intake, micronutrient deficiencies, and the increasing prevalence of overweight and obesity. Limited knowledge of balanced nutrition contributes to unhealthy eating behaviors and may negatively affect children's growth, health, and academic performance. This community engagement program aimed to improve balanced nutrition knowledge among elementary school students through an interactive nutrition education intervention. The program was conducted at SDN Bareng 1, Bojonegoro Regency, East Java, involving 21 sixth-grade students. Educational activities consisted of a pre-test assessment, nutrition education using PowerPoint presentations and leaflets, interactive discussions, and a nutrition-themed snakes and ladders game designed to reinforce key messages. Participants’ knowledge was evaluated using a 10-item questionnaire administered before and after the intervention. The results demonstrated an improvement in students’ nutrition knowledge following the educational program. Prior to the intervention, 28.6% of participants were categorized as having poor nutrition knowledge, while 71.4% had good knowledge. After the intervention, all participants (100%) achieved the good knowledge category. The findings suggest that combining conventional educational approaches with interactive game-based learning can effectively enhance nutrition knowledge among school-aged children. This program highlights the potential of school-based nutrition education as a practical strategy to promote healthy eating habits and support long-term nutritional well-being among children